Assessment of medication adherence among Lebanese adult patients with non-communicable diseases during COVID-19 lockdown: a cross-sectional study - Diana Malaeb; Diana Malaeb; Hala Sacre; Sara Mansour; Chadia Haddad; Chadia Haddad; Abir Sarray El Dine; Tamara Fleihan; Souheil Hallit; Souheil Hallit; Souheil Hallit; Pascale Salameh; et al. (Frontiers Media S.A., 2023)
BackgroundMedical treatment is considered a cornerstone in non-communicable diseases (NCDs) management, lack of adherence remains the main challenge that may compromise optimal therapeutic outcome achievement.PurposeThis study aimed to evaluate treatment adherence levels and associated factors among Lebanese adult patients with non-communicable diseases.Materials and methodsA cross-sectional survey conducted during the COVID-19 lockdown imposed by the Lebanese Government (between September 2020 and January 2021) enrolled 263 adult patients through an anonymous online questionnaire to assess adherence to medications using the Lebanese Medication Adherence Scale (LMAS-14).ResultsOf the total sample, 50.2% showed low adherence with a total mean adherence score of 4.41 ± 3.94. The results showed that depression (β = 1.351) and peptic ulcer (β = 1.279) were significantly associated with higher LMAS scores (lower adherence). However, age between 50 and 70 (β = −1.591, p = 0.011), practicing physical exercise (β = −1.397, p = 0.006), having kidney disease (β = −1.701, p = 0.032), and an intermediate (β = −1.336, p = 0.006) to high income (β = −3.207, p < 0.001) were significantly associated with lower LMAS scores (higher adherence).ConclusionOur study shed light on the factors affecting medication adherence in patients with non-communicable diseases. It showed that depression and peptic ulcer were associated with lower adherence, contrary to older age, exercising, having chronic kidney disease, and a higher socioeconomic status.